2021
DOI: 10.1186/s12891-021-04626-6
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative prognostic nutritional index is useful factor for predicting postoperative delirium after primary total joint arthroplasty

Abstract: Background Postoperative delirium (PD), as an acute brain failure, is widely reported as a very common postoperative complication, and it is closely associated with increased morbidity and mortality. Recently, malnutrition is reported as one of the risk factors for PD. The prognostic nutritional index (PNI) is a simple method for nutritional evaluation. However, few studies have discussed the effectiveness of PNI as a nutritional assessment in predicting PD after primary total joint arthroplast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 31 publications
2
17
0
Order By: Relevance
“…Previous studies have reported that electrolyte disorders (particularly hyponatremia) and malnutrition are risk factors for delirium and postoperative delirium 23,24 . In the present study, the DST‐positive rate increased as the serum K level decreased.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Previous studies have reported that electrolyte disorders (particularly hyponatremia) and malnutrition are risk factors for delirium and postoperative delirium 23,24 . In the present study, the DST‐positive rate increased as the serum K level decreased.…”
Section: Discussionsupporting
confidence: 60%
“…Previous studies have reported that electrolyte disorders (particularly hyponatremia) and malnutrition are risk factors for delirium and postoperative delirium. 23,24 In the present study, the DST-positive rate increased as the serum K level decreased. It is possible that hypokalemia prevented the maintenance of intracellular volume, rapidly destroying the balance in osmolality and resulting in fluid abnormalities such as dehydration.…”
Section: Discussionsupporting
confidence: 53%
“…Our meta-analysis showed lower PNI values among patients in the POD group (MD: −3.78, 95% CI: −4.85 to −2.71, p < 0.0001, I 2 = 54.2%) compared to those in the non-POD group (Figure 3) (25,29,(35)(36)(37)(39)(40)(41). In the six studies (25,29,36,37,39,40) that used PNI as a continuous parameter for POD risk prediction, multivariable logistic regression was adopted as the analytical tool. Pooled results showed that a higher PNI was associated with a lower risk of POD (OR: 0.91, 95% CI: 0.86-0.97, p = 0.002, I 2 = 71%) (Figure 4).…”
Section: Results Of Syntheses 321 Primary Outcome: Association Betwee...mentioning
confidence: 73%
“…After deleting duplicate records and those that failed to meet our inclusion criteria from the 188 articles originally retrieved from the databases, we selected 38 potentially eligible studies for a full-text review that further excluded 29 articles (Figure 1). Finally, nine retrospective studies published between 2010 and 2021 involving 3,743 patients were included for the present meta-analysis (25,29,(35)(36)(37)(38)(39)(40)(41).…”
Section: Selection Characteristics and Quality Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation